Influence of Small-Sided Games and Motor Ability in Performance Games Development - Aditya Pahlevi; Ali Munir (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The purpose of this study is to be able to determine whether there is an influence of small sided games and motor ability on athlete performance in volleyball games. The method in this study is an experimental method where the design of this study uses factorial design. The results of this study show that small-sided games training methods, block system programs and random system programs have a significant effect on games performance, small-sided games training has interactions with motor ability that have different effects on games. While the small-sided games training method block system and random system programs have a significant effect on games performance in the high motor ability group, small-sided games training methods, block system programs and random system programs, do not have a significant effect on games performance in the low motor ability group. So that in providing volleyball training programs, especially the random system program, it should be given to athletes who have high motor ability. But for low motor ability can be used both programs, both block system programs and random system programs. Keywords: Performance Games, Small-Sided Games, Motor Ability, Volleyball Information System